2021
DOI: 10.1111/jnu.12660
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Outcomes of Nurses’ Subjective Career Success: A Path Analysis

Abstract: Accessible healthcare services require a sufficient number of well-educated and well-motivated nurses who can provide quality and safe healthcare services (Simoens, Villeneuve, & Hurst, 2005). The global shortage of nurses reveals the importance of jobs that meet employees' career development needs and provide an opportunity for progress (Burke, Johnson, Sites, & Barnsteiner, 2017). Spurk, Keller, and have reported that employees with successful careers have a higher sense of welfare and job satisfaction (JS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 37 publications
0
43
1
Order By: Relevance
“…This finding contradicts the results of previous studies, which believed that both individual and environmental factors affect career success (Spurk et al, 2019). For example, age is one of the demographic characteristics that is considered an important variable related to career success (Sönmez et al, 2021;Spurk et al, 2019). In this study, age could not predict changes in career success variance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding contradicts the results of previous studies, which believed that both individual and environmental factors affect career success (Spurk et al, 2019). For example, age is one of the demographic characteristics that is considered an important variable related to career success (Sönmez et al, 2021;Spurk et al, 2019). In this study, age could not predict changes in career success variance.…”
Section: Discussioncontrasting
confidence: 99%
“…Existing studies show that not only individual factors but also work-related factors affect career success. Societal norms like salary, job level, promotion history, or job prestige (Spurk et al, 2019) and environmental factors like relationship with co-workers and having the necessary equipment and facilities to do the job are among work-related factors that impact career success (Sönmez et al, 2021). In addition, resources that support coping with expected and unexpected challenges and harms are considered critical to achieving career success (Spurk et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The subjective criteria include the individual's career satisfaction and their perceived competitiveness within and outside the organization. Studies have indicated (Sonmez et al, 2021) that the higher the career satisfactions of nurses, the lower their intention to leave and the higher their sense of career success. Nursing managers can use career success as an intrinsic motivation to form and stabilize their nursing team.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it can be found that there are significant differences in demographics in terms of nurses’ years of work, title, administrative position, marital status, and department. As can be seen in Table 1 , the career success scores of nurses with advanced titles are significantly higher than those nurses with other titles, which may be related to the fact that nurses with advanced titles are more mature and stable in terms of work experience, knowledge, and technical level compared to nurses with other two titles ( Sönmez et al, 2021 ). Moreover, with the improvement of titles, the salary and competitiveness of nurses within the organization will be further improved, which is more conducive to their career development and therefore they have higher career success scores.…”
Section: Discussionmentioning
confidence: 97%
“…Nurses’ career success refers to the unity of positive subjective feelings and objective outcomes of clinical nurses in their career ( Heslin, 2005 ). Studies have shown that career success, as a key protective factor for nurses’ career development, has positive effects in reducing nursing brain drain and ensuring the quality of nursing service ( Sönmez et al, 2021 ; Xu et al, 2021 ). The results of this study show that the median total score of career success of female nurses in central China is 68, which is in the medium level, lower than the results of Dan’s study on career success of nurses in mainland China, indicating that there is still some room for improvement ( Dan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%